2017
DOI: 10.21859/sija-1202242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elder abuse in Iran: a systematic review and meta analysis

Abstract: Objectives Abuse of older people is a major issue in societies that can reduce self-confidence, generate feelings of hopelessness and apathy, and cause psychological disability in the elderly. The purpose of this study is to determine the prevalence of elder abuse in Iran. Methods & MaterialsThis study is a systematic review and meta-analysis, in which all articles about elderly abuse in Iran since 2005-2014 were searched using online databases such as MEDLINE, Google Scholar, SID, Web of Science, and Magiran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
0
27
1
Order By: Relevance
“…However, the prevalence of this problem in the family setting was approximately 25%, while in the institutional setting it was between 11% and 24% [6]. A study in Iran found that the overall prevalence of elder abuse was 56.4%, and its highest and lowest prevalence rates were reported in Tehran (87.8%) and Shahrekord (17.1%) Provinces, respectively [16]. Manouchehri et al [17] revealed that 84.4% of elderly people visiting the parks of Tehran (in Iran) had experienced a form of emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence of this problem in the family setting was approximately 25%, while in the institutional setting it was between 11% and 24% [6]. A study in Iran found that the overall prevalence of elder abuse was 56.4%, and its highest and lowest prevalence rates were reported in Tehran (87.8%) and Shahrekord (17.1%) Provinces, respectively [16]. Manouchehri et al [17] revealed that 84.4% of elderly people visiting the parks of Tehran (in Iran) had experienced a form of emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yon et al [7] reported that psychological abuse, financial abuse, neglect, physical abuse, and sexual abuse were the most common types of elder abuse, respectively, while physical, social, emotional, financial, and sexual abuse, along with the violation of personal rights and neglect, were the most common types of elder abuse, respectively, in the present study. In a meta-analysis, Molaei et al [16] found that emotional abuse was the most frequent type of elder abuse, although discrepancies exist in the included studies. They further reported the prevalence of different types of abuse of older adults as follows: neglect (4.5-68.0%), mental abuse (12.4-59.8%), financial mismanagement (5.8-40.0%), physical misconduct (2.8-35.9%), and isolation (3.7-23.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Available data suggest that the overall elder abuse prevalence in Iran is 56.4% with confidence interval 95% (35.1-75.5%) [21]. It is concluded; Iranian's nurses encounter with and take care of elderly patients who have experience abuse.…”
Section: Introductionmentioning
confidence: 96%
“…It includes 57 items and 7 subscales including psychological misbehavior (6items), authority deprivation (7items) physical misbehaviours (2 items), nancial misbehaviours (11 items), being abandoned (4 items), caring neglect (8 items) and emotional misbehavior (19 items). The tool is scored through a 4 point likert scale with the options of never (1), sometimes (2), often (3) and always (4). Scores range between 1 to 228.…”
Section: Data Collectionmentioning
confidence: 99%